Answer:
Explanation:
Let say the following:
p = number of points
We know that they scored the same number of points in Game 1 and Game 2.
But in Game 3, they scored 6 points less than Game 1 and Game 2.
Therefore,
Game 1 = p
Game 2 = p
Game 3 = p - 6
To find the average you use the following formula:
Number of points / number of games = average
Basically,
(Game 1 + Game 2 + Game 3 ) / 3 = 63
So substitute the equations we made earlier and you get:
![(Game 1 + Game 2 + Game 3)/(3) = 63\\(p + p + (p - 6))/(3) = 63](https://img.qammunity.org/2021/formulas/mathematics/high-school/nt8cxxe7wq97tdtuyrbh3aibe57r6teofv.png)
After this you just want to solve for "p"
Multiply both sides by 3 to get rid of the fraction:
p + p + (p - 6) = 63 x 3 = 189
3p - 6 = 189
Add 6 to both sides.
3p = 189 + 6 = 195
Divide both sides by 3
p = 195/3 = 65
So now we know p = 65 points. Substitute this back into our equations for each game:
Game 1 = p , Game 1 = 65 points
Game 2 = p , Game 2 = 65 points
Game 3 = p - 6 , Game 3 = 65 - 6 = 59 points